The Abdominal Aortic Aneurysm and Intraluminal Thrombus: Current Concepts of Development and Treatment - Piechota-Polanczyk, Aleksandra; Jozkowicz, Alicja; Nowak, Witold; Eilenberg, Wolf; Neumayer, Christoph; Malinski, Tadeusz; Huk, Ihor; Brostjan, Christine (Frontiers in Cardiovascular Medicine, 2015)
The pathogenesis of the abdominal aortic aneurysm (AAA) shows several hallmarks of atherosclerotic and atherothrombotic disease, but comprises an additional, predominant feature of proteolysis resulting in the degradation and destabilization of the aortic wall. This review aims to summarize the current knowledge on AAA development, involving the accumulation of neutrophils in the intraluminal thrombus and their central role in creating an oxidative and proteolytic environment. Particular focus is placed on the controversial role of heme oxygenase 1/carbon monoxide and nitric oxide synthase/peroxynitrite which may exert both protective and damaging effects in the development of the aneurysm. Treatment indications as well as surgical and pharmacological options for AAA therapy are discussed in light of recent reports.